Chapter Effects of petroleum hydrocarbons on Salicornia perennans germination and growth under saline conditions - Lazzeri, Valerio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The research studied the effects of petroleum hydrocarbons (PHs) on Salicornia perennans Willd. at different saline concentrations. The study investigated 1) in vitro germination and 2) plants growth in hydroponics conditions. PHs, together with salinity, strongly affected the germination. Under saline conditions, PHs generally stimulated germination in terms of time and final rate. Plant growth and the photosynthetic performance were significantly affected at 0 g/l of salt and with high PHs addition. Hence, the saline conditions seem to be necessary to enable the resistance to the PHs stress.